2021
DOI: 10.1186/s12302-021-00493-z
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of nanoparticles from nano-enabled products for the protection of cultural heritage surfaces: a review

Abstract: The development of highly innovative techniques and technologies to enhance performance and technical sustainability of materials used in the field of cultural heritage conservation is providing conservators with innovative nanocomposites materials, including protective coatings, by merging the performances of engineered nanoparticles (NPs) with conventional chemicals. However, the human health and environmental risks that may potentially arise from these new materials are still largely unknown, requiring an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…Only a negligible level of leaching was reported with the magnitude of 0.0024 mg l −1 and 0.0038 mg l −1 respectively for the 24 weeks weathered DT40 and DK40 coating systems for the water samples that were collected under simulated rainfall conditions with the angle of 45° water falling angle. This value is within the safe limits of world health organization's drinking water quality standards [51] and hence there is no risk of leaching out of nano‐TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Only a negligible level of leaching was reported with the magnitude of 0.0024 mg l −1 and 0.0038 mg l −1 respectively for the 24 weeks weathered DT40 and DK40 coating systems for the water samples that were collected under simulated rainfall conditions with the angle of 45° water falling angle. This value is within the safe limits of world health organization's drinking water quality standards [51] and hence there is no risk of leaching out of nano‐TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A solution of 0.1 M Ag NPs was prepared as a positive control according to previous studies , (further details can be found in the Supporting Information). Hydrogels were completely submerged in DI water and vortexed lightly for 1 min to emulate industrially relevant conditions such as weathering and mechanical strain . Hydrogels remained submerged for one week, and the wash solutions were then measured using a Carry 500 UV–vis–NIR spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogels were completely submerged in DI water and vortexed lightly for 1 min to emulate industrially relevant conditions such as weathering and mechanical strain. 24 Hydrogels remained submerged for one week, and the wash solutions were then measured using a Carry 500 UV−vis−NIR spectrophotometer. The samples were compared to a stock Ag NP solution prepared as detailed in the Supporting Information due to the presence of the characteristic peak of silver around 400 nm, 25 which could be used for comparison with the experimental samples.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…As explained in the review by Brunelli et al, 2021, leaching tests can be performed according to standard protocols (International Organization for Standardization, 2018;The British Standards Institution, 2004) by a partial or a total immersion of the nano-enabled product in a liquid, followed by the quantification of NPs and/or its ionic form at different time of immersion (for a maximum of 4 weeks). The reported standard protocols have been developed for nanobased paints and paints debris.…”
Section: Analytical Techniques and Methods Used To Test The Sbd Alter...mentioning
confidence: 99%